(untitled) (Medical Forum Monthly, 2023)
Objective: It was to determine the in-vitro antibacterial activity of ethanolic leaf extracts of Tinospora cordifolia (TC) and Solanum nigrum (SN) against Multidrug resistant- Escherichia coli (MDR-E.coli). Study Design: In-vitro experimental study. Place and Duration of Study: This study was conducted at the Pharmacology Department, Ziauddin University, Karachi from December 2022 to May 2023. Materials and Methods: TC and SN leaves were extracted using a rotary evaporator. Antibacterial sensitivity of both extracts was determined by Agar well diffusion assay and the Broth Dilution assay. Results: Total 8 concentrations from 3.90 to 500 mg/ml were made in 10% DMSO for both the extracts. No significant antibacterial activity was observed against MDR-E.coli at any tested concentration. Conclusion: The leaf extracts of Solanum nigrum and Tinospora cordifolia were ineffective against MDR- E.coli of DFI.